الصوامت في اللغتين العربية والإندونيسية: دراسة تقابلية - Royani, Ahmad; Nawawi, Mukhshon; Farhah, Ourora Nida (Department of Arabic Education - Faculty of Educational Sciences, 2023)
This article aims to explain the similarities and differences between Arabic and Indonesian consonant letters, as well as the steps in teaching them. This research uses contrastive analysis, which compares two languages to find out the similarities and differences between the two languages. This research reveals that there are similarities and differences between consonants in Arabic and consonants in Indonesian. The similarities of consonants in Arabic and Indonesian are divided into 2 parts, namely Al Aswat Al Mutamatsilah (exactly the same) and Al Aswat Al Mutasyabihah (similar). In Al Aswat Al Mutamatsilah, consonants in Arabic and Indonesian have similarities both in makhraj, properties and pronunciation. The consonant letters included in Al Aswat Al Mutamatsilah are B and ب, M and م, W and و, F and ف. J and ج, K and ك, R and ر, Z and ز, S and س, H and ه. Meanwhile, in Al Aswat Al Mutasyabihah, consonants in Arabic and Indonesian have one of the differences both in terms of makhraj and nature. The consonant letters that include Al Aswat Al Mutasyabihah are T and ت, D and د, N and ن, L and ل, Y and ي, G and غ, H and ح, K and خ, K and ق, S and ش, S and ث, Z and ذ, S and ص. The consonant differences in Arabic and Indonesian are divided into 3 parts, namely Al Aswat Al Mutakholifah, namely ض and D, ظ and D, ظ and z, ط and T, خ and H. The letters in Arabic that have no equivalent in Indonesian are ث، ح، خ، ذ، ش، ص، ض، ط، ظ، ع، غ، ق. The letters in Indonesian that have no equivalent in Arabic are P, C, Ny, Ng, shawamit tsanaiyah, shawamit tsalatsiyah. In this difference, consonant letters in Arabic and Indonesian have differences in terms of makhraj and properties. Based on this comparison, the teaching of Arabic consonant letters for Indonesian students starts from letters that have similarities and proceeds to letters that have differences.